PERBEDAAN PETA PIKIRAN DAN PETA KONSEP TERHADAP HASIL BELAJAR SISWA PADA EKSPONEN - Siti Salamah Br Ginting; Fitry Wahyuni (Universitas Islam Negeri Imam Bonjol Padang, 2022)
Factors that affect students' mathematics learning outcomes include the lack of student interest in mathematics. Learning that does not have meaning and the teacher's teaching methods are still less diverse, causing a lack of student interest in learning mathematics. One of the meaningful learning is when students can make their own notes from their understanding while studying. This study aims to determine the differences in mathematics learning outcomes of students who are taught using the mind map method and students who are taught with the concept map method. This research was conducted at a private senior high school in Medan. This type of research is a quasi-experimental research design using randomize pretest-posttest control group design. The sampling technique uses purposive sampling by taking two experimental classes in class X high school. The instrument used to determine student learning outcomes on exponent material is a test in the form of an objective test of 15 items that have been declared valid and reliable. The results showed that the average student learning outcomes taught using the mind map method were higher than those taught with the concept map. From the results of this study teachers are expected to use the mind map method to improve student mathematics learning.